SOSIALISASI KEAMANAN DIGITAL KEPADA SISWA BERKEBUTUHAN KHUSUS DI SEKOLAH INKLUSI PKBM HOUSE OF KNOWLEDGE - Alfred Reyner; Tabah Ujianto; Iis aisyah (Abdi Jurnal Publikasi, 2024)
The seminar "Smart Teens in the Digital Era: The Importance of Understanding Internet Security and Privacy Protection" aims to enhance the understanding of digital security among special needs students at PKBM House of Knowledge. This seminar provides knowledge about steps to protect personal data, recognize cyber threats, and apply best practices for online privacy. Using interactive methods, the activities include material delivery sessions, discussions, quizzes, evaluations, and distribution of practical guides. Evaluation results indicate that the seminar successfully increased participants' understanding of digital security, achieving an average score of 91% on a scale of 1-5. This activity is expected to serve as a reference for similar efforts in the future to create a digitally secure and inclusive educational ecosystem.